Investing in the Health and Well-Being of Young Adults - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Young adulthood - ages approximately 18 to 26 - is a critical period of development with long-lasting implications for a person's economic security, health and well-being. Young adults are key contributors to the nation's workforce and military services and, since many are parents, to the healthy development of the next generation. Although 'millennials' have received attention in the popular media in recent years, young adults are too rarely treated as a distinct population in policy, programs, and research. Instead, they are often grouped with adolescents or, more often, with all adults. Currently, the nation is experiencing economic restructuring, widening inequality, a rapidly rising ratio of older adults, and an increasingly diverse population. The possible transformative effects of these features make focus on young adults especially important. A systematic approach to understanding and responding to the unique circumstances and needs of today's young adults can help to pave the way to a more productive and equitable tomorrow for young adults in particular and our society at large. Investing in The Health and Well-Being of Young Adults describes what is meant by the term young adulthood, who young adults are, what they are doing, and what they need. This study recommends actions that nonprofit programs and federal, state, and local agencies can take to help young adults make a successful transition from adolescence to adulthood. According to this report, young adults should be considered as a separate group from adolescents and older adults. Investing in The Health and Well-Being of Young Adults makes the case that increased efforts to improve high school and college graduate rates and education and workforce development systems that are more closely tied to high-demand economic sectors will help this age group achieve greater opportunity and success. The report also discusses the health status of young adults and makes recommendations to develop evidence-based practices for young adults for medical and behavioral health, including preventions. What happens during the young adult years has profound implications for the rest of the life course, and the stability and progress of society at large depends on how any cohort of young adults fares as a whole. Investing in The Health and Well-Being of Young Adults will provide a roadmap to improving outcomes for this age group as they transition from adolescence to adulthood.
Keywords: Health and Medicine; Behavioral and Social Sciences

Community Programs to Promote Youth Development - National Research Council; Institute of Medicine (The National Academies Press, 2002)
After-school programs, scout groups, community service activities, religious youth groups, and other community-based activities have long been thought to play a key role in the lives of adolescents. But what do we know about the role of such programs for today's adolescents? How can we ensure that programs are designed to successfully meet young people's developmental needs and help them become healthy, happy, and productive adults? Community Programs to Promote Youth Development explores these questions, focusing on essential elements of adolescent well-being and healthy development. It offers recommendations for policy, practice, and research to ensure that programs are well designed to meet young people's developmental needs. The book also discusses the features of programs that can contribute to a successful transition from adolescence to adulthood. It examines what we know about the current landscape of youth development programs for America's youth, as well as how these programs are meeting their diverse needs. Recognizing the importance of adolescence as a period of transition to adulthood, Community Programs to Promote Youth Development offers authoritative guidance to policy makers, practitioners, researchers, and other key stakeholders on the role of youth development programs to promote the healthy development and well-being of the nation's youth.
Keywords: Behavioral and Social Sciences; Health and Medicine

Food Marketing to Children and Youth: Threat or Opportunity? - Institute of Medicine (The National Academies Press, 2006)
Creating an environment in which children in the United States grow up healthy should be a high priority for the nation. Yet the prevailing pattern of food and beverage marketing to children in America represents, at best, a missed opportunity, and at worst, a direct threat to the health prospects of the next generation. Children’s dietary and related health patterns are shaped by the interplay of many factors—their biologic affinities, their culture and values, their economic status, their physical and social environments, and their commercial media environments—all of which, apart from their genetic predispositions, have undergone significant transformations during the past three decades. Among these environments, none have more rapidly assumed central socializing roles among children and youth than the media. With the growth in the variety and the penetration of the media have come a parallel growth with their use for marketing, including the marketing of food and beverage products. What impact has food and beverage marketing had on the dietary patterns and health status of American children? The answer to this question has the potential to shape a generation and is the focus of Food Marketing to Children and Youth. This book will be of interest to parents, federal and state government agencies, educators and schools, health care professionals, industry companies, industry trade groups, media, and those involved in community and consumer advocacy.
Keywords: Food and Nutrition

Parenting Matters: Supporting Parents of Children Ages 0-8 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Decades of research have demonstrated that the parent-child dyad and the environment of the family—which includes all primary caregivers—are at the foundation of children's well- being and healthy development. From birth, children are learning and rely on parents and the other caregivers in their lives to protect and care for them. The impact of parents may never be greater than during the earliest years of life, when a child's brain is rapidly developing and when nearly all of her or his experiences are created and shaped by parents and the family environment. Parents help children build and refine their knowledge and skills, charting a trajectory for their health and well-being during childhood and beyond. The experience of parenting also impacts parents themselves. For instance, parenting can enrich and give focus to parents' lives; generate stress or calm; and create any number of emotions, including feelings of happiness, sadness, fulfillment, and anger. Parenting of young children today takes place in the context of significant ongoing developments. These include: a rapidly growing body of science on early childhood, increases in funding for programs and services for families, changing demographics of the U.S. population, and greater diversity of family structure. Additionally, parenting is increasingly being shaped by technology and increased access to information about parenting. Parenting Matters identifies parenting knowledge, attitudes, and practices associated with positive developmental outcomes in children ages 0-8; universal/preventive and targeted strategies used in a variety of settings that have been effective with parents of young children and that support the identified knowledge, attitudes, and practices; and barriers to and facilitators for parents' use of practices that lead to healthy child outcomes as well as their participation in effective programs and services. This report makes recommendations directed at an array of stakeholders, for promoting the wide-scale adoption of effective programs and services for parents and on areas that warrant further research to inform policy and practice. It is meant to serve as a roadmap for the future of parenting policy, research, and practice in the United States.
Keywords: Behavioral and Social Sciences

Improving Access to Oral Health Care for Vulnerable and Underserved Populations - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Access to oral health care is essential to promoting and maintaining overall health and well-being, yet only half of the population visits a dentist each year. Poor and minority children are less likely to have access to oral health care than are their nonpoor and nonminority peers. Older adults, people who live in rural areas, and disabled individuals, uniformly confront access barriers, regardless of their financial resources. The consequences of these disparities in access to oral health care can lead to a number of conditions including malnutrition, childhood speech problems, infections, diabetes, heart disease, and premature births. Improving Access to Oral Health Care for Vulnerable and Underserved Populations examines the scope and consequences of inadequate access to oral health services in the United States and recommends ways to combat the economic, structural, geographic, and cultural factors that prevent access to regular, quality care. The report suggests changing funding and reimbursement for dental care; expanding the oral health work force by training doctors, nurses, and other nondental professionals to recognize risk for oral diseases; and revamping regulatory, educational, and administrative practices. It also recommends changes to incorporate oral health care into overall health care. These recommendations support the creation of a diverse workforce that is competent, compensated, and authorized to serve vulnerable and underserved populations across the life cycle. The recommendations provided in Improving Access to Oral Health Care for Vulnerable and Underserved Populations will help direct the efforts of federal, state, and local government agencies; policy makers; health professionals in all fields; private and public health organizations; licensing and accreditation bodies; educational institutions; health care researchers; and philanthropic and advocacy organizations.
Keywords: Health and Medicine

Weight Gain During Pregnancy: Reexamining the Guidelines - Institute of Medicine; National Research Council (The National Academies Press, 2009)
As women of childbearing age have become heavier, the trade-off between maternal and child health created by variation in gestational weight gain has become more difficult to reconcile. Weight Gain During Pregnancy responds to the need for a reexamination of the 1990 Institute of Medicine guidelines for weight gain during pregnancy. It builds on the conceptual framework that underscored the 1990 weight gain guidelines and addresses the need to update them through a comprehensive review of the literature and independent analyses of existing databases. The book explores relationships between weight gain during pregnancy and a variety of factors (e.g., the mother's weight and height before pregnancy) and places this in the context of the health of the infant and the mother, presenting specific, updated target ranges for weight gain during pregnancy and guidelines for proper measurement. New features of this book include a specific range of recommended gain for obese women. Weight Gain During Pregnancy is intended to assist practitioners who care for women of childbearing age, policy makers, educators, researchers, and the pregnant women themselves to understand the role of gestational weight gain and to provide them with the tools needed to promote optimal pregnancy outcomes.
Keywords: Health and Medicine; Food and Nutrition

Preventing Bullying Through Science, Policy, and Practice - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Bullying has long been tolerated as a rite of passage among children and adolescents. There is an implication that individuals who are bullied must have "asked for" this type of treatment, or deserved it. Sometimes, even the child who is bullied begins to internalize this idea. For many years, there has been a general acceptance and collective shrug when it comes to a child or adolescent with greater social capital or power pushing around a child perceived as subordinate. But bullying is not developmentally appropriate; it should not be considered a normal part of the typical social grouping that occurs throughout a child's life. Although bullying behavior endures through generations, the milieu is changing. Historically, bulling has occurred at school, the physical setting in which most of childhood is centered and the primary source for peer group formation. In recent years, however, the physical setting is not the only place bullying is occurring. Technology allows for an entirely new type of digital electronic aggression, cyberbullying, which takes place through chat rooms, instant messaging, social media, and other forms of digital electronic communication. Composition of peer groups, shifting demographics, changing societal norms, and modern technology are contextual factors that must be considered to understand and effectively react to bullying in the United States. Youth are embedded in multiple contexts and each of these contexts interacts with individual characteristics of youth in ways that either exacerbate or attenuate the association between these individual characteristics and bullying perpetration or victimization. Recognizing that bullying behavior is a major public health problem that demands the concerted and coordinated time and attention of parents, educators and school administrators, health care providers, policy makers, families, and others concerned with the care of children, this report evaluates the state of the science on biological and psychosocial consequences of peer victimization and the risk and protective factors that either increase or decrease peer victimization behavior and consequences.
Keywords: Behavioral and Social Sciences

Building Capacity to Reduce Bullying: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Bullying - long tolerated as just a part of growing up - finally has been recognized as a substantial and preventable health problem. Bullying is associated with anxiety, depression, poor school performance, and future delinquent behavior among its targets, and reports regularly surface of youth who have committed suicide at least in part because of intolerable bullying. Bullying also can have harmful effects on children who bully, on bystanders, on school climates, and on society at large. Bullying can occur at all ages, from before elementary school to after high school. It can take the form of physical violence, verbal attacks, social isolation, spreading rumors, or cyberbullying. Increased concern about bullying has led 49 states and the District of Columbia to enact anti-bullying legislation since 1999. In addition, research on the causes, consequences, and prevention of bullying has expanded greatly in recent decades. However, major gaps still exist in the understanding of bullying and of interventions that can prevent or mitigate the effects of bullying. Building Capacity to Reduce Bullying is the summary of a workshop convened by the Board on Children, Youth, and Families of the Institute of Medicine and National Research Council in April 2014 to identify the conceptual models and interventions that have proven effective in decreasing bullying, examine models that could increase protective factors and mitigate the negative effects of bullying, and explore the appropriate roles of different groups in preventing bullying. This report reviews research on bullying prevention and intervention efforts as well as efforts in related areas of research and practice, implemented in a range of contexts and settings, including schools, peers, families, communities, laws and public policies, and technology. Building Capacity to Reduce Bullying considers how involvement or lack of involvement by these sectors influences opportunities for bullying, and appropriate roles for these sectors in preventing bullying. This report highlights current research on bullying prevention, considers what works and what does not work, and derives lessons learned.
Keywords: Behavioral and Social Sciences

Confronting Commercial Sexual Exploitation and Sex Trafficking of Minors in the United States - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Every day in the United States, children and adolescents are victims of commercial sexual exploitation and sex trafficking. Despite the serious and long-term consequences for victims as well as their families, communities, and society, efforts to prevent, identify, and respond to these crimes are largely under supported, inefficient, uncoordinated, and unevaluated. Confronting Commercial Sexual Exploitation and Sex Trafficking of Minors in the United States examines commercial sexual exploitation and sex trafficking of U.S. citizens and lawful permanent residents of the United States under age 18. According to this report, efforts to prevent, identify, and respond to these crimes require better collaborative approaches that build upon the capabilities of people and entities from a range of sectors. In addition, such efforts need to confront demand and the individuals who commit and benefit from these crimes. The report recommends increased awareness and understanding, strengthening of the law's response, strengthening of research to advance understanding and to support the development of prevention and intervention strategies, support for multi-sector and interagency collaboration, and creation of a digital information-sharing platform. A nation that is unaware of these problems or disengaged from solutions unwittingly contributes to the ongoing abuse of minors. If acted upon in a coordinated and comprehensive manner, the recommendations of Confronting Commercial Sexual Exploitation and Sex Trafficking of Minors in the United States can help advance and strengthen the nation's emerging efforts to prevent, identify, and respond to commercial sexual exploitation and sex trafficking of minors in the United States.
Keywords: Behavioral and Social Sciences

Transforming the Financing of Early Care and Education - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
High-quality early care and education for children from birth to kindergarten entry is critical to positive child development and has the potential to generate economic returns, which benefit not only children and their families but society at large. Despite the great promise of early care and education, it has been financed in such a way that high-quality early care and education have only been available to a fraction of the families needing and desiring it and does little to further develop the early-care-and-education (ECE) workforce. It is neither sustainable nor adequate to provide the quality of care and learning that children and families need—a shortfall that further perpetuates and drives inequality. Transforming the Financing of Early Care and Education outlines a framework for a funding strategy that will provide reliable, accessible high-quality early care and education for young children from birth to kindergarten entry, including a highly qualified and adequately compensated workforce that is consistent with the vision outlined in the 2015 report, Transforming the Workforce for Children Birth Through Age 8: A Unifying Foundation. The recommendations of this report are based on essential features of child development and early learning, and on principles for high-quality professional practice at the levels of individual practitioners, practice environments, leadership, systems, policies, and resource allocation.
Keywords: Behavioral and Social Sciences; Education

Transforming the Workforce for Children Birth Through Age 8: A Unifying Foundation - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Children are already learning at birth, and they develop and learn at a rapid pace in their early years. This provides a critical foundation for lifelong progress, and the adults who provide for the care and the education of young children bear a great responsibility for their health, development, and learning. Despite the fact that they share the same objective - to nurture young children and secure their future success - the various practitioners who contribute to the care and the education of children from birth through age 8 are not acknowledged as a workforce unified by the common knowledge and competencies needed to do their jobs well. Transforming the Workforce for Children Birth Through Age 8 explores the science of child development, particularly looking at implications for the professionals who work with children. This report examines the current capacities and practices of the workforce, the settings in which they work, the policies and infrastructure that set qualifications and provide professional learning, and the government agencies and other funders who support and oversee these systems. This book then makes recommendations to improve the quality of professional practice and the practice environment for care and education professionals. These detailed recommendations create a blueprint for action that builds on a unifying foundation of child development and early learning, shared knowledge and competencies for care and education professionals, and principles for effective professional learning. Young children thrive and learn best when they have secure, positive relationships with adults who are knowledgeable about how to support their development and learning and are responsive to their individual progress. Transforming the Workforce for Children Birth Through Age 8 offers guidance on system changes to improve the quality of professional practice, specific actions to improve professional learning systems and workforce development, and research to continue to build the knowledge base in ways that will directly advance and inform future actions. The recommendations of this book provide an opportunity to improve the quality of the care and the education that children receive, and ultimately improve outcomes for children.
Keywords: Behavioral and Social Sciences

New Directions in Child Abuse and Neglect Research - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Each year, child protective services receive reports of child abuse and neglect involving six million children, and many more go unreported. The long-term human and fiscal consequences of child abuse and neglect are not relegated to the victims themselves—they also impact their families, future relationships, and society. In 1993, the National Research Council (NRC) issued the report, Under-standing Child Abuse and Neglect, which provided an overview of the research on child abuse and neglect. New Directions in Child Abuse and Neglect Research updates the 1993 report and provides new recommendations to respond to this public health challenge. According to this report, while there has been great progress in child abuse and neglect research, a coordinated, national research infrastructure with high-level federal support needs to be established and implemented immediately. New Directions in Child Abuse and Neglect Research recommends an actionable framework to guide and support future child abuse and neglect research. This report calls for a comprehensive, multidisciplinary approach to child abuse and neglect research that examines factors related to both children and adults across physical, mental, and behavioral health domains—including those in child welfare, economic support, criminal justice, education, and health care systems—and assesses the needs of a variety of subpopulations. It should also clarify the causal pathways related to child abuse and neglect and, more importantly, assess efforts to interrupt these pathways. New Directions in Child Abuse and Neglect Research identifies four areas to look to in developing a coordinated research enterprise: a national strategic plan, a national surveillance system, a new generation of researchers, and changes in the federal and state programmatic and policy response.
Keywords: Behavioral and Social Sciences; Health and Medicine

Strengthening the Military Family Readiness System for a Changing American Society - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The U.S. military has been continuously engaged in foreign conflicts for over two decades. The strains that these deployments, the associated increases in operational tempo, and the general challenges of military life affect not only service members but also the people who depend on them and who support them as they support the nation – their families. Family members provide support to service members while they serve or when they have difficulties; family problems can interfere with the ability of service members to deploy or remain in theater; and family members are central influences on whether members continue to serve. In addition, rising family diversity and complexity will likely increase the difficulty of creating military policies, programs and practices that adequately support families in the performance of military duties. Strengthening the Military Family Readiness System for a Changing American Society examines the challenges and opportunities facing military families and what is known about effective strategies for supporting and protecting military children and families, as well as lessons to be learned from these experiences. This report offers recommendations regarding what is needed to strengthen the support system for military families.
Keywords: Behavioral and Social Sciences

Advancing the Power of Economic Evidence to Inform Investments in Children, Youth, and Families - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In recent years, the U.S. federal government has invested approximately $463 billion annually in interventions that affect the overall health and well-being of children and youth, while state and local budgets have devoted almost double that amount. The potential returns on these investments may not only be substantial but also have long-lasting effects for individuals and succeeding generations of their families. Ideally, those tasked with making these investments would have available to them the evidence needed to determine the cost of all required resources to fully implement and sustain each intervention, the expected returns of the investment, to what extent these returns can be measured in monetary or nonmonetary terms, and who will receive the returns and when. As a result of a number of challenges, however, such evidence may not be effectively produced or applied. Low-quality evidence and/or a failure to consider the context in which the evidence will be used may weaken society's ability to invest wisely, and also reduce future demand for this and other types of evidence. Advancing the Power of Economic Evidence to Inform Investments in Children, Youth, and Families highlights the potential for economic evidence to inform investment decisions for interventions that support the overall health and well-being of children, youth, and families. This report describes challenges to the optimal use of economic evidence, and offers recommendations to stakeholders to promote a lasting improvement in its quality, utility, and use.
Keywords: Behavioral and Social Sciences

Sports-Related Concussions in Youth: Improving the Science, Changing the Culture - Institute of Medicine; National Research Council (The National Academies Press, 2014)
In the past decade, few subjects at the intersection of medicine and sports have generated as much public interest as sports-related concussions - especially among youth. Despite growing awareness of sports-related concussions and campaigns to educate athletes, coaches, physicians, and parents of young athletes about concussion recognition and management, confusion and controversy persist in many areas. Currently, diagnosis is based primarily on the symptoms reported by the individual rather than on objective diagnostic markers, and there is little empirical evidence for the optimal degree and duration of physical rest needed to promote recovery or the best timing and approach for returning to full physical activity. Sports-Related Concussions in Youth: Improving the Science, Changing the Culture reviews the science of sports-related concussions in youth from elementary school through young adulthood, as well as in military personnel and their dependents. This report recommends actions that can be taken by a range of audiences - including research funding agencies, legislatures, state and school superintendents and athletic directors, military organizations, and equipment manufacturers, as well as youth who participate in sports and their parents - to improve what is known about concussions and to reduce their occurrence. Sports-Related Concussions in Youth finds that while some studies provide useful information, much remains unknown about the extent of concussions in youth; how to diagnose, manage, and prevent concussions; and the short- and long-term consequences of concussions as well as repetitive head impacts that do not result in concussion symptoms. The culture of sports negatively influences athletes' self-reporting of concussion symptoms and their adherence to return-to-play guidance. Athletes, their teammates, and, in some cases, coaches and parents may not fully appreciate the health threats posed by concussions. Similarly, military recruits are immersed in a culture that includes devotion to duty and service before self, and the critical nature of concussions may often go unheeded. According to Sports-Related Concussions in Youth, if the youth sports community can adopt the belief that concussions are serious injuries and emphasize care for players with concussions until they are fully recovered, then the culture in which these athletes perform and compete will become much safer. Improving understanding of the extent, causes, effects, and prevention of sports-related concussions is vitally important for the health and well-being of youth athletes. The findings and recommendations in this report set a direction for research to reach this goal.
Keywords: Health and Medicine

The Promise of Adolescence: Realizing Opportunity for All Youth - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Adolescence—beginning with the onset of puberty and ending in the mid-20s—is a critical period of development during which key areas of the brain mature and develop. These changes in brain structure, function, and connectivity mark adolescence as a period of opportunity to discover new vistas, to form relationships with peers and adults, and to explore one's developing identity. It is also a period of resilience that can ameliorate childhood setbacks and set the stage for a thriving trajectory over the life course. Because adolescents comprise nearly one-fourth of the entire U.S. population, the nation needs policies and practices that will better leverage these developmental opportunities to harness the promise of adolescence—rather than focusing myopically on containing its risks. This report examines the neurobiological and socio-behavioral science of adolescent development and outlines how this knowledge can be applied, both to promote adolescent well-being, resilience, and development, and to rectify structural barriers and inequalities in opportunity, enabling all adolescents to flourish.
Keywords: Behavioral and Social Sciences; Health and Medicine